Comparison of Short, Intermediate, and Long Cephalomedullary Nail Length Outcomes in Elderly Intertrochanteric Femur Fractures. (March 2022) - Womble, Tanner N.; Kirk, Andrew; Boyle, Maxwell; Comadoll, Shea M.; Su, Leon; Srinath, Arjun; Matuszewski, Paul Edward; Aneja, Arun
Abstract : Introduction: Cephalomedullary nail (CMN) length for intertrochanteric femur fractures without subtrochanteric extension has been an ongoing debate. The authors hypothesize that increasing nail length would result in increasing surgical time, greater incidence of acute kidney injury (AKI), postoperative anemia, and blood loss requiring transfusion due to increased intramedullary reaming and pressurization of the canal with nail insertion. Methods: A retrospective chart review of patients aged 65 years or older who underwent CMN for low-energy intertrochanteric femur fractures from 2010 to 2018 was undertaken. Patient demographic data, comorbidities, case duration, postoperative hospital length of stay (LOS), and laboratory data, including serum creatinine, hemoglobin, and hematocrit, were collected for analysis. The following outcome measures were compared: postoperative pneumonia, cardiac complications, sepsis, reintubation/intensive care unit stay, pulmonary embolism, stroke, postoperative AKI, 30-day hospital readmission, 30-day return to operating room, 30-day mortality, 1-year mortality, postoperative anemia (hemoglobin <7 g/dL), and blood transfusion. Results: A total of 247 patients were analyzed (short = 48, intermediate = 39, and long = 160). No notable difference was observed in postoperative pneumonia, cardiac complications, sepsis, reintubation/intensive care unit stay, pulmonary embolism, stroke, mean total hospital LOS, mean postoperative hospital LOS, rate of postoperative AKI, 30-day readmission, 30-day return to operating room, 30-day mortality, or 1-year mortality. Patients receiving long nails had significantly higher rates of postoperative anemia ( P = 0.0491), blood transfusion ( P = 0.0126), and mean procedure length ( P = 0.0044) compared with the two other groups. Discussion: Patients receiving long nails had markedly higher rates of postoperative anemia and blood loss requiring blood transfusion with markedly longer mean procedure length than patients receiving short and intermediate CMNs. Long nails did not result in an increase in other complications evaluated.